Chest physiotherapy after cardiac surgery - the missing link - S. de Charmoy; C. J. Eales (AOSIS, 1997)
The physiotherapy literature pertaining to the treatment of cardiac surgery patients in the period 1977 to 1995 was reviewed. The purpose of this review was to analyse the results of the research and draw up guidelines for the physiotherapy treatment of cardiac surgery patients. This review revealed that there is no indication for routine chest physiotherapy in the uncomplicated cardiac surgery patient.